Theoretical Study on Passively Mode-Locked Fiber Lasers with Saturable Absorber - Nady, Ahmed; Mathkoor, F.H.; Harun, Sulaiman Wadi (Taylor & Francis, 2019)
In this paper, passively mode-locked erbium-doped fiber lasers based on saturable absorber (SA) have been theoretically studied. The energetics and pulse properties for different fiber laser cavity configurations have been investigated and the effects of each component (active fiber, passive fiber, and SA) in the laser cavity have been studied. This numerical study takes into account the temporal change in the saturable absorption (dq/dt).The presented simulations could be highly useful for understanding, optimizing, and improving passively mode-locked fiber lasers with SA. © 2018, © 2018 Taylor & Francis.